Solar‐PV augmented wind energy generation system with improved efficiency control of doubly fed induction generator through adjustable stator frequency. (12th November 2020) - Parida, Adikanda; Singh, Yogendra; Chatterjee, Debashis
Summary: The proposed work addresses the improved efficiency control of doubly fed induction generator (DFIG) connected to common DC‐link. The improved efficiency condition is obtained considering DFIG stator frequency as the degree of freedom. The adjustable stator frequency is obtained for minimum iron and copper losses of DFIG. The higher efficiency not only improves energy production from the same input but also increases life and reduces the occurrence of a fault in the machine. In this paper, a comparatively simple technique has been developed which facilitates appropriate augmentation of solar‐PV with the proposed DFIG based wind energy generation system (WEGS) through an automatic power exchange between DC‐link and AC‐link of the system. This not only helps to mitigate issues related to active power fluctuation in the existing WEGS but also maintains DC‐link voltage constant irrespective of the load variation in the DC‐link. Also in this paper, an MRAS based sensorless DFIG rotor position online measurement technique has been adopted which is more accurate in comparison to the existing techniques with insignificantly dependent on machine parameter variations. The developed control technique is successfully validated through proper simulation and experiments on a scaled prototype setup with 2.5 kW DFIG, 2.5 kW polycrystalline solar‐PV, and dSPACE CP1104 module, which produced satisfactory results. Abstract : The proposed work addresses the improved efficiency control of doubly fed induction generator (DFIG) connected to common DC‐link. The improved efficiency condition is obtained considering DFIG stator frequency as the degree of freedom. The adjustable stator frequency is obtained for minimum iron and copper losses of DFIG. The higher efficiency not only improves energy production from the same input but also increases life and reduces the occurrence of a fault in the machine. In this paper, a comparatively simple technique has been developed which facilitates appropriate augmentation of solar‐PV with the proposed DFIG based wind energy generation system (WEGS) through an automatic power exchange between DC‐link and AC‐link of the system. This not only helps to mitigate issues related to active power fluctuation in the existing WEGS but also maintains DC‐link voltage constant irrespective of the load variation in the DC‐link. Also in this paper, an MRAS based sensorless DFIG rotor position online measurement technique has been adopted which is more accurate in comparison to the existing techniques with insignificantly dependent on machine parameter variations. The developed control technique is successfully validated through proper simulation and experiments on a scaled prototype setup with 2.5kW DFIG, 2.5kW polycrystalline solar‐PV, and dSPACE CP1104 module, which produced satisfactory results.